Bridging may help young female Tibetan macaques Macaca thibetana learn to be a mother. Issue 1 (December 2018) - Zhang, Dao; Xia, Dong-Po; Wang, Xi; Zhang, Qi-Xin; Sun, Bing-Hua; Li, Jin-Hua
Abstract Attraction to infants is a common feature of non-human primates. Frequent affiliative male-infant interactions have been observed in many multimale, multifemale groups of macaques, including a behaviour termed 'bridging' in which two male macaques simultaneously lift an infant. This behaviour has been suggested to serve as a positive affiliative interaction between the adult or subadult males. Female macaques display bridging in the same manner as males, but the function of this behaviour to females remains unknown. In this study, we examined evidence for the function and evolution of bridging in female Tibetan macaques within the framework of three hypotheses: the learning to mother, a side-effect of selection for appropriate maternal care, and alliance formation hypotheses. Our results showed that subadult females initiated more bridging than adult females. Females preferred to use infants for bridging when the infants were less than four weeks old. Female frequency of received bridging with higher-ranking females was not significantly different from their frequency of received bridging with lower-ranking females. Bridging frequency was not significantly different between dyads composed of related and unrelated females. Additionally, post-bridging grooming frequency was significantly higher than nonbridging grooming interactions, suggesting a social function for bridging. The results of our study supported the 'learning to mother' hypothesis, suggesting that bridging among female intrasexual dyads is a multi-functional, complex and differential evolutionary process.